SAT0109 Accelerated Subclinical Atheromatosis, but not Arterial Stiffness or Hypertrophy, in Rheumatoid Arthritis Patients Free of Classical Risk Factors. (10th June 2014) - Arida, A.; Zampeli, E.; Konstantonis, G.; Fragkiadaki, K.; Kitas, G.D.; Protogerou, A.D.; Sfikakis, P.P.
Abstract : Background: Several lines of evidence indicate that classical cardiovascular disease (CVD) risk factors, such as arterial hypertension, diabetes mellitus, smoking and dyslipidemia, are significantly increased in rheumatoid arthritis (RA), which, in turn, is associated with 1.5- to 2-fold increased prevalence of CVD. The exact contribution of the RA disease per se in this association, in terms of systemic inflammation, drugs, disease-related genetics and/or other factors, remains under study. Objectives: We aimed to test the hypothesis that RA per se in patients free of classical CVD risk factors is associated with accelerated subclinical arterial disease. Methods: Consecutive patients with RA (n=267) were comprehensively studied by ultrasound for, a) subclinical atheromatosis assessed by the presence of carotid artery and/or femoral artery plaques, b) stiffness of common carotid artery and aortic stiffness by pulse wave velocity, and, c) hypertrophy of common carotid artery assessed by intimal-medial thickness and cross sectional area (calculated adjacent to plaques, when plaques were present). Of all patients, we identified those who were CVD-free, non-smokers, without hypertension, diabetes and dyslipidemia (only 18%). Of them, 41 (aged 49±13 years, 36 women, median disease duration of 7 years, range 3-19 years) were compared to 41 healthy non-smokers, without hypertension, diabetes and dyslipidemia who were effectively matched 1:1 for age and gender and studied in parallel. Results: Patients had more than 2-fold higher prevalence of carotid and/or femoral atheromatic plaques than healthy controls (29% vs. 12%, p=0.05). All patients with plaques had an acceptable functional status of class I or II. Moreover, body mass index, as well as family history of CVD, was similar between patients with plaques and their matched controls. Multi-arterial subclinical atheromatosis, defined as plaque presence at more than 1 of 8 arterial sites evaluated, was by far more prevalent in RA patients than controls (22% vs. 2%, p=0.007). Notably, plaque burden in the subgroup of RA patients with less than 5 years of disease duration was comparable to their matched controls. Either arterial stiffness or hypertrophy, however, was not significantly increased compared to controls, even in patients with long-standing RA. Conclusions: These data directly show for the first time an acceleration of atheromatosis in RA, but not of arterial stiffness or hypertrophy, independently of the classical CVD risk factors. This phenomenon is not evidenced during the first 5 years after disease onset and seems to be chronic inflammation-dependent. Also, the dissociation between atheromatosis and arterial stiffness in this selected population suggests a minimal, if any, effect of chronic inflammation in arterial remodeling. Studies testing whether early and effective RA clinical disease control prevents the development of arterial damage in the long-term are ongoing. Disclosure of Interest: None declared DOI: 10.1136/annrheumdis-2014-eular.5811